2018
DOI: 10.1097/pai.0000000000000483
|View full text |Cite
|
Sign up to set email alerts
|

Discordance Rate in Estrogen Receptor, Progesterone Receptor, HER2 Status, and Ki67 Index Between Primary Unifocal and Multiple Homogenous Breast Carcinomas and Synchronous Axillary Lymph Node Metastases Have an Impact on Therapeutic Decision

Abstract: Background:We aimed to demonstrate that in breast carcinomas the tumor profile is not stable during the metastatic process, with impact on therapeutic decisions.Materials and Methods:We analyzed the estrogen receptor (ER), progesterone receptor (PR), and HER2 status and Ki67 index in 41 primary unifocal (PU) and 37 primary multiple (PM) breast carcinomas with identical immunohistochemical profiles among multiple tumor foci and the matched axillary lymph node metastases. We defined as concordant cases in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Typically, but not always, such alterations are associated with progression on ET therapy. Multiple independent studies have in fact reported significant HR discordance rates between primary breast tumours and matched metastatic lesions [134][135][136][137][138][139][140] (Fig. 4, part II), highlighting several issues.…”
Section: Key Determinants Of Relapse In Hr + Breast Cancermentioning
confidence: 99%
“…Typically, but not always, such alterations are associated with progression on ET therapy. Multiple independent studies have in fact reported significant HR discordance rates between primary breast tumours and matched metastatic lesions [134][135][136][137][138][139][140] (Fig. 4, part II), highlighting several issues.…”
Section: Key Determinants Of Relapse In Hr + Breast Cancermentioning
confidence: 99%
“…There are a number of biological changes that can occur as the cancer progresses to the nodes, though the rate at which this happens is unclear. Some studies have suggested discordance between the primary and nodal cancer happens often-more than 30% for ER, 40% for PR and 24% for HER2 [108]-and others say it is not often enough to warrant evaluating biomarkers in all positive nodes [109,110], and yet others suggest it is somewhere in between [111,112]. To definitively characterise nodal metastases, it may be necessary to evaluate the same biomarkers in cancerous nodal tissue in addition to the primary tumour, as this information could change the treatment plan for some patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies had demonstrated ER, PR and HER2 status instability between primary breast cancer and synchronous axillary lymph node metastasis (Aitken et al, 2010;Rossi et al, 2015). Furthermore, some article recommended to determination of hormone receptors and HER2 status in both primary tumor and synchronous axillary nodal metastasis to guide therapy management and evaluate the recurrent risk also (Lower et al, 2017;Georgescu et al, 2018).…”
Section: The Case To Case Comparison Of Hormone Receptors and Her2 Stmentioning
confidence: 99%